Glyphosate-Resistant Italian Ryegrass (Lolium perenne ssp. multiflorum) Control with Fall-Applied Residual Herbicides. (June 2014) - Bond, Jason A.; Eubank, Thomas W.; Bond, Robin C.; Golden, Bobby R.; Edwards, H. Matthew
Abstract : Dense populations of glyphosate-resistant (GR) Italian ryegrass are problematic for spring burndown herbicide programs and crop establishment in the midsouthern United States. Two field studies were conducted to evaluate fall-applied residual herbicides for control of GR Italian ryegrass and to identify the most effective application timing for these herbicides. Fall applications of clomazone at 0.84 and 1.12 kg ai ha −1, pyroxasulfone at 0.16 kg ai ha −1, and S -metolachlor at 1.79 kg ai ha −1 controlled GR Italian ryegrass ≥ 93% 180 d after application. Control from incorporated applications of pendimethalin at 1.59 kg ai ha −1 and trifluralin at 1.68 kg ai ha −1 and surface applications of S -metolachlor at 1.42 kg ha −1 provided control similar to the best treatments. Glyphosate-resistant Italian ryegrass control following clomazone, pyroxasulfone, S -metolachlor, or trifluralin applied in mid September, October, or November exceeded that from fall tillage by 19 to 56% at 90 and 140 d after the last treatment. Pyroxasulfone and S -metolachlor controlled more GR Italian ryegrass following October or November applications compared with those in September at both 90 and 140 d after the last application timing. However, the benefit of delaying clomazone application from October to November was not realized until the last evaluation (140 d after the last treatment). Clomazone, pyroxasulfone, and S -metolachlor offer growers the best opportunity for residual control of GR Italian ryegrass, and control is optimized when these herbicides are applied in November.